Root canal therapy used in conjunction with follow‐ups for the nonsurgical handling of an enormous periapical lesion of endodontic origin: Clinical case record - Nitin R. Rao; Abdul Mujeeb; Aishwarya A. Kottur; Ankita Mathur; Niher Tabassum Siddiqua Snigdha; Mohmed Isaqali Karobari (Clinical Case Reports, 2024)
Key Clinical Message The main objective of root canal therapy is to locate all the canals, cleaning, and shaping, and obturation to obtain fluid tight seal and to heal the periapical lesion if present. Abstract The proper cleaning, shaping, and disinfection of the pulp chambers, as well as the filling of the canals, are critical to the efficacy of treatment with root canals. The success of an endodontically treated tooth is dependent on the accuracy of the diagnosis, disinfection, cleaning and shaping, obturation, and finally, the prosthetic rehabilitation management. Root canal therapy should provide a hermatic as well as fluid impenetrable seal which prevents the progression of periapical infection. There are two ways to treat such lesions: surgical and nonsurgical methods. If the root canal is cleaned, shaped, and sealed properly and adequately without the use of a surgical procedure, these lesions will recover during nonsurgical root canal therapy. This case series focuses primarily on the nonsurgical treatment of an enormous periapical lesion and provides evidence that these lesions respond well without surgery.